An evaluation of the effectiveness of a 'Five Ways to Well‐being' group run with people with learning disabilities. (11th November 2016) - Mahoney‐Davies, Gerwyn; Dixon, Clare; Tynan, Hannah; Mann, Sian
Abstract : Accessible summary: The Five Ways to Well‐being is a document produced by the government which gives advice about things people can do to improve how they feel. These five things are being with people, being active, noticing things around you, to keep learning and giving to others. We taught a group of adults with learning disabilities how to do these five things. We had ten sessions which lasted 2 h each. We did not find that people felt better after the ten sessions, but we did find that they noticed more things around them which may help improve their well‐being. People found the group useful. Abstract: Background: The 'Five Ways to Well‐being' document presents five ways in which people in the general population may be able to improve their well‐being. This study evaluates the use of a 'Five Ways to Well‐being' group in a population of people with learning disabilities. Materials and Methods: Twelve participants who attend a day support service engaged in a ten‐week group programme based on the Five Ways to Well‐being. Scores on the Rosenberg Self‐Esteem Scale and Short Warwick‐Edinburgh Mental Well‐being Scale provided a baseline, and scores at the first, middle and final session were entered into repeated measures analysis of variance or nonparametric equivalents. Results: Scores suggest there was no difference between baseline and final session on either of these scales ( P  > 0.05). There was a significant difference between baseline and final session on a clinician‐devised measure of well‐being of the aims of the group (F(2, 18) = 3.6, P  = 0.049), and this effect is likely to be carried by an increase in the group's use of mindfulness skills. Qualitative feedback suggests that the group was useful and prompted changes in participants' well‐being. Conclusions: Participants found the group useful, and scores suggest an increase in mindfulness practice, but there is no evidence that running a Five Ways to Well‐being group with people with learning disabilities will improve their well‐being. However, this was not a clinical group of people with mental health concerns, and conclusions cannot be made about the usefulness of the model in this population.